SOCIO-PSYCHOLOGICAL FACTORS DEFINING THE ATTITUDE OF RUSSIAN PEOPLE TOWARDS PRENUPTIAL AGREEMENT - Sergeeva, Anna; Pryaluhina, Alla; Tuzova, Olga; Tuchkova, Tamara (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In the modern world the institution of family and marriage is undergoing various changes. The attitude of Russian people towards the prenuptial agreement shows a tendency for acceptance and approval. The stereotypical perception of the prenuptial agreement as unacceptable between close people is in the past. Based on that, the article is focused on the comparative analysis of the factors that define the attitude of Russian people towards the prenuptial agreement. The key point in the research is evaluation of specific features of respondents’ opinions, expressed in the years of 2007 and 2018, in accordance with the following socio-psychological factors: awareness of the prenuptial agreement, aims for signing one or reasons to refuse doing so, gender and age factors. Research methods include: a preliminary survey of couples in order to define sample groups, a questionnaire, observation, a mathematical method of data analysis (Fisher’s φ-criterion). The research was conducted in two stages: the first diagnostics in the year 2007 (n=40 couples), and the second – in 2018 (n=50 couples). The respondents were divided into groups by the social status of their relationships: officially married, planning to get married, co-habiting couples and partner (guest) relationships. The age of respondents was 18-47. The results of the research showed the following: increase in age leads to clearer understanding and a better expressed opinion about the prenuptial agreement, positive dynamics in favourable perception of prenuptial agreement among the respondents who are officially married or are planning to marry, increased importance of motives for signing a prenuptial agreement – “protection of one’s own interests” and “opportunity to put pressure on the spouse”, lack of connection between the attitude towards prenuptial agreement and awareness of the document.